2012
DOI: 10.9734/bjmmr/2012/1002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mycobacterium tuberculosis 16 and 71 Heat Shock Proteins in the Cerebrospinal Fluid of Tuberculous Meningitis Patients

Abstract: Aims: To evaluate the efficiency of two potential Mycobacterium tuberculosis (M. tb) heat shock proteins (Hsps) towards the improvement of tuberculous meningitis (TBM) diagnosis. Study Design: The patients were divided into TBM (confirmed and suspected) and non TBM group. The cerebrospinal fluid (CSF) was collected and evaluated for M. Research ArticleBritish Journal of Medicine & Medical Research, 2(2): 243-253, 2012 244 with PCR technique and concordance was also calculated. Of the Hsp ELISA positive gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Our results showed that the levels of host Hsp25, Hsp60, Hsp70, and Hsp90 and MTB Hsp16 were significantly increased in the TB group compared to the high-risk exposure, lowrisk exposure and healthy control groups, which is consistent with our previous reports [14,21,22]. However, an even more interesting finding of this study is the increased levels of the same panel of Hsp(s), which are considered to be ''danger signals,'' in the sera of the high-risk exposure group compared to the low-risk exposure and healthy control groups.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results showed that the levels of host Hsp25, Hsp60, Hsp70, and Hsp90 and MTB Hsp16 were significantly increased in the TB group compared to the high-risk exposure, lowrisk exposure and healthy control groups, which is consistent with our previous reports [14,21,22]. However, an even more interesting finding of this study is the increased levels of the same panel of Hsp(s), which are considered to be ''danger signals,'' in the sera of the high-risk exposure group compared to the low-risk exposure and healthy control groups.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, the host Hsp(s) should be increased in the high-risk exposure group, where the chances of disease are the greatest compared to the low-risk exposure group and healthy controls. It is well known that bacterial Hsp(s) are highly immunogenic and capable of inducing antibody production and T cell activation [14,21,30]. MTB Hsp16 is required for the survival of bacteria in the stationary phase, and therefore, the maintenance of a constant cellular level of this protein is an important strategy for MTB to survive in the dormant state [35].…”
Section: Parameters [Mean With Sd] Tb (N = 10)mentioning
confidence: 99%
See 1 more Smart Citation